Narratives Of Sexuality In Bugis And Makasar Manuscripts - Hadrawi, Muhlis (Penerbit Universiti Sains Malaysia (USM Press), 2016)
This paper discusses a particular category of text called assikalaibineng, which contain a range of Bugis and Makasar knowledge relating to sexual procedure and relations for married couples. The sexual knowledge in these texts was mainly restricted to members of Sufi tariqa, in particular the elite, and assikalaibineng sexual knowledge was shaped by both indigenous practices and Islamic values and Sufi teachings. In this paper, I focus on the following assikalaibineng sexual knowledge: the ideology and symbols of assikalaibineng, actions to be taken by newlyweds, and the detailed threestage procedure a couple should follow during sexual intercourse. In addition, I discuss the Sufi links to assikalaibineng knowledge and the problematic textual transmission of this knowledge.